Considerations and proposals for the management of patients after prolonged intensive care unit admission. Issue 1019 (10th August 2010) - Johns, Robin H; Dawson, Deborah; Ball, Jonathan
Abstract : The majority of patients admitted to the intensive care unit (ICU) have a short stay of only a few days. However a small but significant number require prolonged intensive care. This is typically due to persisting, and sometimes complex, medical/surgical problems. Discharge of such ICU patients requires a comprehensive, multidisciplinary, verbal and written handover to the receiving ward team. As with any acutely ill adult in hospital, post-ICU patients should be carefully monitored with 'track and trigger' systems such as the Early Warning Score. Those with unexpected physiological deterioration should be promptly reviewed by senior clinicians and/or medical emergency/critical care outreach teams and considered for ICU re-admission where appropriate. Patients who have received prolonged organ support in the ICU are often affected by a number of specific medical problems such as ventilatory insufficiency, cardiac dysfunction, kidney injury, nutritional deficiency, ICU acquired weakness, and brain injury. They also frequently experience physical disability and psychosocial problems including delirium, anxiety, depression, post-traumatic stress disorder, cognitive dysfunction, and disturbed sleep. Structured rehabilitation programmes for post-ICU patients, tailored to individual needs, should be commenced on the ICU and continued through to and beyond hospital discharge. Care bundles, which are widely used on the ICU, are groups of interventions employed to optimise treatments or minimise complication rates. They may be additionally useful in the post-ICU ward setting by prompting clinicians to focus on, and address, commonly occurring medical and psychosocial problems in these patients.